APLICATION OF RECITATION METHOD BASED ON PAKEM AS EFFORTS TO IMPROVE STUDENT UNDERSTANDING OF THE CURRICULUM CONCEPT IN THE PGMIPABI PROGRAM AT PHYSICS EDUCATION - Sahidu, Hairunisyah; ., Kosim; ., Hikmawati (Jurnal Lembaga Penelitian Universitas Mataram, 2014)
Students understanding about the curriculum concept (Education Unit Level Curriculum) or Kurikulum Tingkat Satuan Pendidikan (KTSP) is not optimal. Students tend to get information about the curriculum through text books or the Internet. Direct observation of the implementation of the curriculum into schools still rarely done. As prospective teachers, students should go directly to the field to conduct visitation how the school curriculum is developed and implemented by parties concerned with the intended curriculum. Application of the method recitation (assignment) in a study based on a Active, Creative, Effective, and Fun Learning or Pembelajaran Aktif, Kreatif, Efektif, dan Menyenangkan (PAKEM) at Review of Curriculum and Content Analysis of Physics I aim to improve student understanding of curriculum concepts and develop devices use traditional methods of lecture with recitation (assignment) based on PAKEM. This research is a class act who performed in two cycles. Each cycle consists of the planning, implementation measures, observation and evaluation, and reflection. The subjects in this study were students taking a course Review of Curriculum and Content Analysis of Physics I in Math and Science Teacher Education Internationally or Pendidikan Guru MIPA Bertarat Internasional (PGMIPABI) program. Data obtained through the understanding of the concept of student evaluation tests given at each end of the cycle, while the student activity data obtained through observation sheet. Indicators of success used in this study is that if 85% of students achieving greater understanding of curriculum concepts or equal to 75. In the first cycle the average value of 82 and students are all completed, while in the second cycle values are the average student is 85. Student activities that most often arises is: "Delivering the opinion / Communicating information to the class or lecturer" by 28% in cycles in cycles I and II by 32%. Thus, application of methods based PAKEM recitation in the lecture can improve student understanding of curriculum concepts.